Surrender - Hardt, Helen (Hardt, Helen. Steel brothers saga, 2017)
Jonah Steel has fallen in love with Melanie Carmichael but refuses to make a commitment until he has solved the mystery of his family<U+2019>s past. A new threat has surfaced, and he needs to eliminate it. Melanie loves Jonah but has yet to surrender completely to his needs. Still, she wants a promise that he can't yet make. While the ghosts of her past still hover around her, she joins him on his quest for answers. Together, they vow to find the truth. But the deeper they dig, the more danger they uncover<U+2026>